Preventive and Therapeutic Effects of the Retinoid X Receptor Agonist Bexarotene on Tumors - Qi, Lisi; Guo, Yuanyuan; Zhang, Pei; Cao, Xiaorong; Luan, Yuxia (Current Drug Metabolism, 2016)
We present a review of recent investigations of anticancer drug bexarotene in this article. As one of the novel synthetic analogs of retinoids, bexarotene selectively binds to and activates the retinoid X receptor (RXRs) subfamilies, exerting a prophylactic and therapeutic effect on a large series of tumors in vitro and in vivo covering cutaneous lesions, lung and breast cancers, nervous system diseases etc. Bexarotene has been proved to have a specifically favorable therapeutic profile in clinical dermatology or oncology with mild or absent retinoids side effects, especially in combination with other therapies. It is noteworthy that numerous previous outstanding researches have contributed to the chemical, biological, preclinical and clinical examinations of bexarotene during the past decades, with a relatively deficient progress of bexarotene in the field of pharmacy. In this review, the positive therapeutic results of bexarotene used as a monotherapy or combination therapy both in preclinical and clinical studies are reported based on relevant medical data; the distinct acting mechanisms of bexarotene are described; the potential studies and prospects of bexarotene in pharmaceutical domain are discussed. All the reports above collectively present bexarotene as a promising anti-cancer agent.
Keywords: combinations